Large-scale mutational analysis of wheat powdery mildew resistance gene Pm21 - He, Huagang; Guo, Rui; Gao, Anli; Chen, Zhaozhao; Liu, Renkang; Liu, Tianlei; Kang, Xusen; Zhu, Shanying (Frontiers in Plant Science, 2022)
Wheat powdery mildew is a devastating disease leading to severe yield loss. The powdery mildew resistance gene Pm21, encoding a nucleotide-binding leucine-rich repeat receptor (NLR) protein, confers broad-spectrum resistance to powdery mildew and has great potential for controlling this disease. In this study, a large-scale mutagenesis was conducted on wheat cultivar (cv.) Yangmai 18 carrying Pm21. As a result, a total of 113 independent mutant lines susceptible to powdery mildew were obtained, among which, only one lost the whole Pm21 locus and the other 112 harbored one- (107) or two-base (5) mutations in the encoding region of Pm21. From the 107 susceptible mutants containing one-base change, we found that 25 resulted in premature stop codons leading to truncated proteins and 82 led to amino acid changes involving in 59 functional sites. We determined the mutations per one hundred amino acids (MPHA) indexes of different domains, motifs, and non-domain and non-motif regions of PM21 protein and found that the loss-of-function mutations occurred in a tendentious means. We also observed a new mutation hotspot that was closely linked to RNBS-D motif of the NB-ARC domain and relatively conserved in different NLRs of wheat crops. In addition, we crossed all the susceptible mutants with Yangmai 18 carrying wild-type Pm21, subsequently phenotyped their F1 plants and revealed that the variant E44K in the coiled-coil (CC) domain could lead to dominant-negative effect. This study revealed key functional sites of PM21 and their distribution characteristics, which would contribute to understanding the relationship of resistance and structure of Pm21-encoded NLR.